2022
DOI: 10.1002/adma.202109984
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Surface Display of mRNA Antigens by Bacteria‐Derived Outer Membrane Vesicles for a Personalized Tumor Vaccine

Abstract: mRNA vaccines can encode one or more tumor specific antigens, derived from genetic mutations, and undergo intracellular protein translation and antigen processing to form complexes with the major histocompatibility complex I (MHCI) in antigen presenting cells (APCs), mainly DC cells (DCs), ultimately presenting the antigens to T cells to induce a robust tumor-specific T cell response. [3,4] This intracellular antigen production and processing approach employed by mRNA vaccines is particularly suitable for a tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 56 publications
0
74
0
1
Order By: Relevance
“…Biological membrane-based vehicles represent another novel biocompatible platform for mRNA delivery. Distinct types of biological membrane-based systems, including cell membrane vesicles 135 , bacteria-derived outer-membrane vesicles 136 and extracellular vesicles 137 (for example, exosomes 138 ), have been employed for in vitro and in vivo delivery of therapeutic mRNAs. As a type of nanoscale extracellular vesicle, exosomes have been widely investigated as carriers for drug delivery 139,140 .…”
Section: Review Articlementioning
confidence: 99%
“…Biological membrane-based vehicles represent another novel biocompatible platform for mRNA delivery. Distinct types of biological membrane-based systems, including cell membrane vesicles 135 , bacteria-derived outer-membrane vesicles 136 and extracellular vesicles 137 (for example, exosomes 138 ), have been employed for in vitro and in vivo delivery of therapeutic mRNAs. As a type of nanoscale extracellular vesicle, exosomes have been widely investigated as carriers for drug delivery 139,140 .…”
Section: Review Articlementioning
confidence: 99%
“…Oral arabinose induces the bacterial robot to produce OMVs carrying tumor antigens in situ in the intestines, thereby activating strong anti-tumor immune responses and immune memory effects (Figure 3D). To expand the application of tumor vaccine types, Li et al 67 have modified RNA binding protein on the surfaces of OMVs through fusion protein expression, and used box C/D sequence-labeled mRNA antigens to adsorb antigens on the surfaces of OMVs. This is the first time that OMVs were successfully been used as an mRNA delivery platform.…”
Section: Tumor Antigen Loadingmentioning
confidence: 99%
“…Recently, it has been reported that the use of Gram-negative bacteria-derived outer-membrane vesicles (OMVs) as an mRNA delivery platform strongly stimulates the innate immune system, promoting antigen presentation and T cell activation. Moreover, OMVs generated after surface modification of the RNA-binding protein L7Ae and the lysosomal escape protein Listerinolysin O (OMV-LL-mRNA) can significantly inhibit tumor progression, induce long-term immune memory, and protect mice from tumor challenges after 60 days [ 135 ].…”
Section: Nucleic Acid Drugs Delivered By Evs For Cancer Therapymentioning
confidence: 99%